2007
DOI: 10.3844/ajbbsp.2007.92.102
|View full text |Cite
|
Sign up to set email alerts
|

The NifX Protein is Involved in the Final Stages of FeMo-cofactor Transport to the MoFe Protein

Abstract: Abstract:The nitrogenase enzyme catalyzes the reduction of dinitrogen to ammonia and is composed of the Fe and MoFe proteins. The iron molybdenum cofactor (FeMo-co) of the MoFe protein is the site of active substrate reduction. The NifX protein has also been suggested to have a role in the FeMo-co synthesis, although its exact role is still open to investigation. We attempted to understand the role of NifX by determining the specific interactions it may have with other Nif proteins involved in FeMo-co synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Two genes, MCHK_2003 and MCHK_5582 , encoding for nitrogen utilization are up-regulated, while all the proteins relative to electron transport and nitrogen fixation ammonia assimilation are down-regulated in the mutant bacteroids. The nitrogenase enzyme is composed of the Fe and MoFe proteins [ 25 ]. Three key nitrogen-fixation genes, nifX , nifD , and nifK , are required for nitrogenase component proteins, and nifE is required for the synthesis of the iron–molybdenum cofactor (FeMoco) of nitrogenase.…”
Section: Resultsmentioning
confidence: 99%
“…Two genes, MCHK_2003 and MCHK_5582 , encoding for nitrogen utilization are up-regulated, while all the proteins relative to electron transport and nitrogen fixation ammonia assimilation are down-regulated in the mutant bacteroids. The nitrogenase enzyme is composed of the Fe and MoFe proteins [ 25 ]. Three key nitrogen-fixation genes, nifX , nifD , and nifK , are required for nitrogenase component proteins, and nifE is required for the synthesis of the iron–molybdenum cofactor (FeMoco) of nitrogenase.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the small molecule binding domain of nifX has a phyletic widespread distribution which indicates an ancient origin or extensive dissemination by horizontal gene transfer during evolution (Lahiri et al 2007). Molecular evolutionary analysis of the chlorophyll biosynthetic pathway strongly supports that the photosystem of the anoxygenic purple bacteria is the most ancient (Xiong et al 2000).…”
Section: Discussionmentioning
confidence: 97%